LAS CONTRADICCIONES AMBIENTALES ENTRE LA POLÍTICA AGRARIA COMÚN (PAC) DE LA UNIÓN EUROPEA Y EL TRATADO TRANSATLÁNTICO DE COMERCIO E INVERSIONES (TTIP) - JOSÉ ANTONIO SEGRELLES (Bollettino della Società Geografica Italiana)
The rigorous environmental standards of the Common Agricultural Policy (CAP) of the European Union (EU) may become worth no more than the paper they are written on if the Transatlantic Trade and Investment Partnership (TTIP) is signed with the United States. These two regions represent mutually opposed ideas, concepts and approaches that would ultimately interact dialectically, the appropriate scientific method to adopt for an analysis of this question. The general aim of this paper is to reflect on the increase in competition that will be sparked by an intensification of free trade, and the consequent escalation of production, degradation of the environment and deterioration in working conditions and food quality; in other words, the categorical worsening of everything that the CAP claims to defend, especially as regards pollution, ecosystem integrity, animal welfare and public health.